The FIMP Medicines for Children Research Network - Napoleone Ettore; Mele Giuseppe (BMC, 2010)
Abstract The European Paediatric Regulation (EUPR) calls for the fostering of high quality ethical research and medicinal products to be used in children. The EUPR provides the background, goals, and requirements for paediatric clinical trials. Paediatric clinical trials in children are mandatory to generate data on new drugs as well as on drugs used off-label or for unlicensed indications. The Family Paediatricians Medicines for Children Research Network (FIMP-MCRN) was established in 2003 with the aim of developing competence, infrastructure, networking and education for paediatric clinical trials. The network, consisting of twenty Paediatric Regional Networks has progressed very well and has achieved valuable improvements concerning the conduct of paediatric clinical trials. Furthermore, ad hoc training programs have incremented knowledge about clinical trials in Family Paediatrician Investigators (FPI) and have made medical professionals as well as the public aware of the need and advantages of trials in children.